2018
DOI: 10.1192/bjp.2018.175
|View full text |Cite|
|
Sign up to set email alerts
|

Mental health outcomes at the end of the British involvement in the Iraq and Afghanistan conflicts: a cohort study

Abstract: BackgroundLittle is known about the prevalence of mental health outcomes in UK personnel at the end of the British involvement in the Iraq and Afghanistan conflicts.AimsWe examined the prevalence of mental disorders and alcohol misuse, whether this differed between serving and ex-serving regular personnel and by deployment status.MethodThis is the third phase of a military cohort study (2014–2016; n = 8093). The sample was based on participants from previous phases (2004–2006 and 2007–2009) and a new randomly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
195
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 190 publications
(227 citation statements)
references
References 37 publications
17
195
6
Order By: Relevance
“…Mental health‐related stigmatization was not associated with SA; however, stigma reduction efforts are often a central feature of suicide reduction campaigns (Niederkrotenthaler, Reidenberg, Till, & Gould, ). The lack of association in our study notwithstanding, given that mental ill health was significantly associated with both SA and SH and recent studies have shown that around 50% of UK AF personnel with mental disorder symptoms do not seek help (Stevelink, Jones, Hull, et al., ), it remains important to ensure that those with mental disorder symptoms are assisted to navigate barriers to care and to engage with evidence‐based treatments.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…Mental health‐related stigmatization was not associated with SA; however, stigma reduction efforts are often a central feature of suicide reduction campaigns (Niederkrotenthaler, Reidenberg, Till, & Gould, ). The lack of association in our study notwithstanding, given that mental ill health was significantly associated with both SA and SH and recent studies have shown that around 50% of UK AF personnel with mental disorder symptoms do not seek help (Stevelink, Jones, Hull, et al., ), it remains important to ensure that those with mental disorder symptoms are assisted to navigate barriers to care and to engage with evidence‐based treatments.…”
Section: Discussioncontrasting
confidence: 52%
“…Phase 2 incorporated existing cohort members, a new random sample of UK AF personnel at risk of operational deployment (the replenishment sample), and a further randomly selected sample of personnel who had undertaken deployment to Afghanistan (Fear et al., ). Phase 3 surveyed existing cohort members and a further randomly selected replenishment sample (Stevelink, Jones, Hull, et al., ). At each study phase, potential cohort participants were identified from military records as belonging to specific subgroups, for instance, regular and reserve forces, personnel who had deployed to Iraq or Afghanistan, male or female gender, and not belonging to special forces.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of military conflict on mental health is well established, for instance several studies have demonstrated the higher prevalence rates of mental health difficulties such as anxiety, depression, posttraumatic stress disorder (PTSD) and substance misuse among veterans compared to that of the general population [1] [2] [3] [4]. A recent study showed an increase in PTSD rates in the UK military from 4% to 6.2% between 2010 and 2018 [1]. When restricted to only veterans (in the UK defined as having completed one day of paid service) the prevalence rate was 9%.…”
Section: Introductionmentioning
confidence: 99%
“…9 Research also suggests that rates of PTSD are highest in veterans who had recently deployed in a combat role to Iraq or Afghanistan. 10 While anyone can develop PTSD following trauma exposure, incidence increases with trauma severity. Other risk factors can include: previous psychiatric disorder; subsequent life stress post-trauma; a history of childhood adversity; low educational attainment; appraisals of the work in operational theatre as being above an individual's trade or experience; and low unit/organisation morale or poor social support.…”
Section: Ptsd Prevalence and Risk Factorsmentioning
confidence: 99%